1993
DOI: 10.3109/03093649309164363
|View full text |Cite
|
Sign up to set email alerts
|

The CAT-CAM socket and quadrilateral socket

Abstract: Twenty unilateral trans-femoral amputees fitted with either the Contoured Adducted Trochanteric-Controlled Alignment Method (CAT-CAM) socket (n=10) or the quadrilateral (QUAD) socket (n=10), and a “non-amputee” control group (n=10) participated in the study. Subjects meeting the following criteria were studied: healthy males between the ages of 18 and 55 years, amputation due to non-vascular pathology, an unaffected sound limb, at least six months use of the test prosthesis, and a minimal stump length of 15 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…A comparison between QUAD and ICS sockets in terms of energy consumption was made by Flandry et al [20], reporting a lower energy expenditure (-56%) in the latter configuration. In addition, Gailey et al [21] showed a 20% lower energy expenditure when using the CAT-CAM socket, with respect to the QUAD one.…”
Section: A Biomechanical Parameters In Lower Limb Amputeesmentioning
confidence: 98%
“…A comparison between QUAD and ICS sockets in terms of energy consumption was made by Flandry et al [20], reporting a lower energy expenditure (-56%) in the latter configuration. In addition, Gailey et al [21] showed a 20% lower energy expenditure when using the CAT-CAM socket, with respect to the QUAD one.…”
Section: A Biomechanical Parameters In Lower Limb Amputeesmentioning
confidence: 98%
“…1,2 The quantification of metabolic energy cost, as an evaluation of the overall efficiency of gait, has been widely used to compare prosthetic elements. [3][4][5][6] However, the reference method of quantification, oxygen consumption, implies the measurement of exhaled gas and cannot always be easily integrated into conventional gait analysis.…”
Section: Introductionmentioning
confidence: 99%
“…31 Comparative study of transfemoral sockets has drawn less attention from researchers than transtibial sockets. Compared to the Quad-S, the ICS results in a lower energy cost of walking, 42 increased walking speed and stride length, 43 more even interface pressure distribution, 44 improved comfort, 45 and less restriction of hip motion. 46 Sub-ischial sockets appear to be comparable to ICS in coronal plane stability and vertical movement, but with lower peak pressure at the proximal-medial brim during gait.…”
Section: Clinical Effectiveness Researchmentioning
confidence: 99%